2020
DOI: 10.1016/j.icarus.2020.113627
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of soluble organic matter: Application to Titan's haze

Abstract: The origin and evolution of organic matter in the solar system intertwines astrobiology and planetary geochemistry issues. To observe the contribution of atmospheric processes in the formation of complex organic matter, one of the most intensively studied objects in the outer solar system is Titan, the largest moon of Saturn. Its reducing atmosphere of methane and nitrogen hosts a thick, permanent, nitrogen-rich, organic haze, whose complex composition remains largely unknown. Due to the measurement of species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…This work confirms structural hypotheses proposed in previous works performed by ion mobility concerning the presence of bulky structures in the soluble molecules (Maillard et al, 2020;Ruger et al, 2019). Such part of these structure were identified in several NMR studies (Derenne et al, 2012;He and Smith, 2014a, b) and liquid-chromatography-mass spectrometry analyses (Gautier et al, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This work confirms structural hypotheses proposed in previous works performed by ion mobility concerning the presence of bulky structures in the soluble molecules (Maillard et al, 2020;Ruger et al, 2019). Such part of these structure were identified in several NMR studies (Derenne et al, 2012;He and Smith, 2014a, b) and liquid-chromatography-mass spectrometry analyses (Gautier et al, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…The more aromatic one will be called series 1 and the other series 2. To illustrate this observation, putative structural formulas of compounds representative of the two major series were added in the Figure. These putative structures are based on hypotheses made in previous works (Gautier et al, 2017;Maillard et al, 2020;Ruger et al, 2019). Two types of aromatic materials are observed by the series 1 and series 2.…”
Section: Fragmentation Of the Species Detected In The Insoluble Fractionmentioning
confidence: 94%
See 1 more Smart Citation
“…Molecules B3, B12, and B8 are very close to structures identified in previous solid-state NMR analyses (He & Smith 2014;McGuigan et al 2006). Structures such as A1, B5, and B9 were hypothesized in recent works (Maillard et al 2020;Ruger et al 2019). Furthermore, as stated above, the observed structures could contain even more nitrogen atoms that are not revealed because of their pronounced no-planarity.…”
Section: Discussionmentioning
confidence: 97%
“…Global analytical techniques gave an overview of the overall structure of the material. Solidphase NMR showed that tholins' structure is mainly based on unsaturated C = N bonds such as imines or triazine units (Derenne et al 2012) and ion mobility highlighted a global structure with a slightly higher double-bond equivalent (DBE) than PAH, more in agreement with a nitrogenated PAH (N-PAH) global structure (Derenne et al 2012;Maillard et al 2020).…”
Section: Introductionmentioning
confidence: 98%